Beef empire carcass merit days index system - T.H. Powell; S.D. Laudert; R.W. Lee; G. Seibert; John A. Unruh; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1992)
Kansas State University, in cooperation with the Beef Empire Days committee, developed a new beef carcass index system for 1991, incorporating yield and quality traits as indicators of carcass merit. Development of the system considered current industry and consumer demands in a critical evaluation of final carcass ranking. The index starts from 100 points and applies positive and negative adjustments for hot carcass weight; ribeye area; adjusted 12th rib fat thickness; percent kidney, pelvic, and heart fat; and quality grade. The index was first used in 1991.
Keywords: Cattlemen& #x27; s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Carcass; Index; Quality; Cutability